Three-dimensional MoS2/Graphene Aerogel as Binder-free Electrode for Li-ion Battery - Yan Zhong; Tielin Shi; Yuanyuan Huang; Siyi Cheng; Chen Chen; Guanglan Liao; Zirong Tang (Nanoscale Research Letters, 2019)
Abstract Hybrid MoS2/reduced graphene aerogels with rich micro-pore are fabricated through a hydrothermal method, followed by freeze-drying and annealing treatment. The porous structure could act as an electrode directly, free of binder and conductive agent, which promotes an improved electron transfer, and provides a 3D network for an enhanced ion transport, thus leading to an increased capacity and stable long cycle stability performance. Notably, the specific capacity of MoS2/reduced graphene aerogel is 1041 mA h g−1 at 100 mA g−1. Moreover, reversible capacities of 667 mA h g−1 with 58.6% capacity retention are kept after 100 cycles. The outstanding performance is beneficial from the synergistic effect of the MoS2 nanostructure and graphene conductive network, as well as the binder-free design. These results provide a route to integrate transition-metal-dichalcogenides with graphene to fabricate composites with rich micro-pores and a three-dimensional network for energy storage devices.